Prevalence, Immune Response and Treatment Of Mite Infestation In Rabits - Regu Ravindran (Department of Parasitology, College of Veterinary and Animal Sciences, 1998)
The prevalence, immune response and treatment of mite infestation in rabbits of Mannuthy and Thrissur, Kerala were studied in detail during a one year period from August 1997 to July 1998. The total prevalence of mange in rabbits was 56.9 per cent. The prevalence increased as temperature decreased, humidity and rainfall increased. The mite infestation was more prevalent during rainy months of the year. Notoedres cuniculi, Psoroptes cuniculi, Listrophorus gibbus and Cheyletiella parasi tivorax were identified as the four species of mites